Del mito de Troya en el espejo de "Tirant lo Blanco" - Alemany, Rafael Alemany Ferrer; Cots Vicente, Montserrat; Monegal, Antonio, 1957- (Barcelona: Universitat Pompeu Fabra, 2010)
El mito de Troya es uno de los motivos literarios que Joanot Martorell recicla en su Tirant lo Blanc, novela cuyo punto de partida es otro motivo recurrente de las letras medievales: el conflicto greco-turco. La Constantinopla de Martorell, asediada por los turcos, se convierte en un revival de la Troya atacada por los griegos. Así se deduce del cotejo del Tirant con la Historia destructionis Troiae, de Guido delle Colonne, de cuya traducción catalana Martorell se sirve profusamente. Las concomitancias entre ambas obras conciernen, fundamentalmente, a los esquemas narrativos amoroso y militar, así como al desenlace trágico. Martorell logra un singular desarrollo novelesco del prestigioso topos medieval del conflicto greco-turco, mediante la fusión productiva de éste con ingredientes del no menos prestigioso topos clásico de la guerra de Troya, originando, así, el nacimiento de un nuevo mito superador de los originarios de que procede. | The Trojan myth is one of the literary motifs that Joanot Marlorell recycles in his Tirant lo Blanc, a novel that takes its cue from another usual motif of the medieval literature: the Greco-Turkish war. Martorell's Constantinople, besieged by the Turks, develops into a revival of the city of Troy attacked by the Greeks. This is deduced thanks to the comparison between Tirant and the Historia destructionis Troiae, by Guido delle Colonne, whose Catalan translation was used by Martorell in a profuse way. The concommittances between both works are related, fundamentally, to the narrative loving and military schemes, as well as to the tragic conc1usion. Martorell achieves a singular fictional development of a prestigious medieval topos of the Greco-Turkish conflict, by means of the productive merger of this one with ingredients of equally prestigious classic topos of the Trojan war, originating, this way, the birth of a new myth superior over the original ones from which it comes.
Keywords: Mito; Troya (Ciudad desaparecida)